2013
DOI: 10.1111/j.1747-0080.2012.01641.x
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding guidance in community pharmacies: The results of a mystery shopper study

Abstract: Aim:  To assess the nature and quality of breastfeeding‐related guidance provided by community‐based pharmacy staff. Methods:  A covert observational ‘mystery shopper’ study of 66 randomly selected community pharmacies was employed to assess actual breastfeeding guidance practices among pharmacy staff. A female mystery shopper used a scripted scenario designed to explore guidance practices relevant to breastfeeding promotion. Pharmacy staff: mystery shopper interactions were documented immediately following th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Out of the 1107 papers in the original search and two added due to quoting the 2006 review, 148 papers met the criteria . Extraction of relevant papers from those found by the search strategy was done jointly by two researchers (IB and PN) and independently by a third researcher (AA).…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 1107 papers in the original search and two added due to quoting the 2006 review, 148 papers met the criteria . Extraction of relevant papers from those found by the search strategy was done jointly by two researchers (IB and PN) and independently by a third researcher (AA).…”
Section: Resultsmentioning
confidence: 99%
“…[8,10] This is in no way a problem limited to Germany because such deficiencies in the advice provided in pharmacies are described many times in the international literature. [23,[29][30][31][32][33][34][35][36][37][38] On the other hand, there are also a few examples internationally of in part appropriate advisory services provided by pharmacies. [39,40] Depending on the particular criteria investigated, there were clear differences apparent in the quality of the advice provided.…”
Section: Discussionmentioning
confidence: 99%
“…These providers felt that when presented with a case for which they did not feel able to adequately provide a recommendation, other providers would be consulted. Community pharmacists are encouraged to play a greater role in maternal health services, including providing breastfeeding guidance, however, their extent of practice in this area needs to be strengthened ( 15 , 21 ). Our results indicated that community pharmacists would be better equipped to advise breastfeeding patients if some of the hurdles of advising were overcome, including access to lactation-specific resources.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature by Hussainy and Dermele ( 11 ) reported that most studies found healthcare providers to have poor knowledge and variable practices mostly guided by personal experience. These themes are further exemplified in studies by Schrempp ( 12 ), Lee ( 13 ), Long and Montouris ( 14 ), Maher and Hughes ( 15 ), and McAuley ( 16 ).…”
Section: Introductionmentioning
confidence: 90%